A comparison of spelling in texting and formal writing. - Barrientos, Sheila Rose Z.
This study, entitled A Comparison of Spelling in Texting and Formal Writing, shows the similarities and differences in spelling by high school students on mobile communication and in formal writing. It also provides educators basic information on whether or not they should worry over the spelling skills of students. And it will somehow shed light on the ongoing debate as to the perceived influence of text messaging on the writing skills of students., The respondents of the study were fourth year students of Palaca-Damilisan National High School. Using essays and text messages written and composed by the high school students, the researchers aimed to describe how high school students construct messages using cellular phone, find out their commonly misspelled words in English language based on the set of words provided by the researchers, and finally to compare the way high school students spell words in text messaging and formal writing. Using the Theory of Planned Behavior of Ajzen (2006) that shows how a person's beliefs, the social pressure to conform to the wishes of others, and perceived ability to carry out the action can affect his behavior such as spelling words in text messaging and formal writing. After the necessary data were gathered, the researchers found that majority of the respondents scored low in spelling in text messaging and scored average in the formal writing. Twenty or 48 percent has a low score both in text messaging and formal writing. Only two respondents got an average score both in text messaging and formal writing, while only one rated high in formal writing but scored low in text messaging. The researchers found out that in text messaging, five of the 15 words in the list were consistently misspelled while in formal writing, the respondents spelled properly all the words except for one, which is irresistible. In addition, respondents used contractions, numbers and symbols as substitute for letters and omitted some vowels in text messaging, while formal writing the respondents do not substitute letters with numbers. The researchers recommend to conduct more studies on the perceived influence of technological advancement such as cellular phone on the word construction in formal writing, improve the questionnaire so as to satisfy other elements stated in the Theory of Planned Behavior, formulate survey questions that will measure the repsondents' English language skills, conduct a study that would compare the spelling skills of cellular phone and non-cellular phone users, and conduct the study on a group of respondents who are cellular phone users and have a high competence in the English language.